Factors Influencing Children's Language Development in Psycholinguistic Theory - Wahyuni, Sry; Mantasiah, Mantasiah (The Future of Education Journal, 2026)
This study examines the factors influencing children's language development within the framework of psycholinguistic theory by integrating both theoretical frameworks and recent empirical findings. The objective of this research was to analyze both internal factors (biological, cognitive, and gender-related) and external factors (family environment, parenting styles, stimulation, and learning media) that affect children's language development. It employed a descriptive qualitative method using a literature review approach. Data were collected from relevant academic sources such as books, peer-reviewed journal articles, and research reports. The analysis was conducted through thematic synthesis to identify patterns and relationships among the factors influencing language development. The findings indicated that children's language development is influenced by a combination of internal factors, such as brain maturation and cognitive abilities, as well as external factors, including social interaction, parenting styles, and provided stimulation. In addition, gender differences contribute to variations in the speed and manner of language acquisition.